A manager's guide to the new world of work the most effective strategies for managing people, teams, and organizations (The MIT Press, 2020)
"This volume examines the micro and macro components of today's companies, from people up to organizations, and the roles and strategies that enable smooth transitions and successful collaboration"--
Includes bibliographical references and index
Keywords: Personnel management; Teams in the workplace; Management -- Technological innovations; Organizational change; Personalpolitik; Digitalisierung; Innovationsmanagement; Teamfähigkeit